The first zinc phosphite with remarkable structural and functional transformations1. Issue 37 (7th May 2015) - Wang, Chih-Min; Chang, Tsung-Yuan; Lee, Li-Wei; Lin, Hsiu-Mei; Lu, Kuang-Lieh; Lii, Kwang-Hwa
<x xml:space="preserve">Abstract</x> An organic–inorganic hybrid zinc phosphite with remarkable structural and functional transformations.